2003
DOI: 10.1073/pnas.0830671100
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptor improves glucose tolerance through coordinate regulation of glucose metabolism in liver and adipose tissue

Abstract: The control of lipid and glucose metabolism is closely linked. The nuclear receptors liver X receptor (LXR)␣ and LXR␤ have been implicated in gene expression linked to lipid homeostasis; however, their role in glucose metabolism is not clear. We demonstrate here that the synthetic LXR agonist GW3965 improves glucose tolerance in a murine model of diet-induced obesity and insulin resistance. Analysis of gene expression in LXR agonist-treated mice reveals coordinate regulation of genes involved in glucose metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
344
4
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 441 publications
(381 citation statements)
references
References 36 publications
29
344
4
4
Order By: Relevance
“…In this work we found that NR1HR agonists increased basal glucose uptake in brown adipocytes in a dosedependent manner, in agreement with the results obtained in 3T3-L1 adipocytes [8]. This effect is the result of changes of SLC2A4 in the plasma membrane, and could be attributed to the activation of PKCζ and/or the increase in Slc2a4 expression produced by T0901317.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this work we found that NR1HR agonists increased basal glucose uptake in brown adipocytes in a dosedependent manner, in agreement with the results obtained in 3T3-L1 adipocytes [8]. This effect is the result of changes of SLC2A4 in the plasma membrane, and could be attributed to the activation of PKCζ and/or the increase in Slc2a4 expression produced by T0901317.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of NR1HR agonists on Slc2a4 expression in rat brown adipocytes is in agreement with the up-regulation of Slc2a4 detected in murine and human adipocytes, where the Slc2a4 promoter is a direct transcriptional target for the NR1HR/RXR heterodimer [8,13]. On the other hand, T0901317 treatment did not produce insulin sensitisation, either on glucose uptake, or in the insulin signalling cascade, an effect clearly different from that observed for rosiglitazone in our previous work [19] and in studies performed in murine adipocytes [8]. Differential effects of pharmacological NR1HR activation on insulin sensitivity in normal or insulin-resistant conditions have also been detected in other studies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations